Impact of external magnetic field on temperature anisotropy driven Weibel instability in a magnetized plasma - Twinkle Pahuja; Amit Kumar; Himank Sagar; Ruby Gupta; Jyotsna Sharma (AIP Advances, 2024)
In this paper, we investigate the impact of an external magnetic field on the Weibel instability driven by temperature anisotropy in a magnetized plasma. The study provides the influence of electron temperature anisotropy, considering both cold as well as warm ions. We derive expressions for the growth rate Γ (s−1) in each case to quantify the effect of some specific parameters on the instability. For example, the growth rate is plotted against the magnetic field for three distinct cases: considering only electrons, including cold ions, and incorporating warm ions. It is observed that the growth rate decreases as the applied magnetic field increases. Furthermore, the addition of both cold and warm ions to the plasma significantly influences the observed effects. It can be explained as follows: in the presence of cold ions, the growth rate is decreased with an increase in the wave number kz (cm−1). In addition, a decrease in the growth rate is observed with an increasing wave number in the case of warm ions. Therefore, it can be seen that the Weibel instability, propelled by thermal anisotropy, holds significant implications owing to its prevalence in both astrophysical and laboratory plasmas. The findings presented here are expected to contribute to the advancements in magnetic field generation and particle acceleration in various astrophysical phenomena, including gamma-ray bursts, relativistic collisionless shock fronts, radio supernovae, and pulsar winds.